Kegagalan Amandemen Pasal 29 UUD 45 dan Masa Depan Syariat Islam - Agus Triyanta (Universitas Islam Indonesia, 2003)
The cancellation of several words in the draft of The State Establishment which is known as Jakarta Charter, i.e. the statement says on the obligation of every muslim to act according the law of Sharia, made great disappointment among Moslems. This fact shows that the eager of Indonesian Muslims to implement their sharia law is extremely huge. Therefore, during the process of constitution amendment in the refor mation era, there was strong tension among representatives whether this words must be attached or not. Even though the effort also failed to remove back the words in to Pancasila, there are still some chances for hospitalization of the implementation of sharia through the local autonomywhich are getting popular today.